Improving staff competences to promote quality of eLearning in Higher Education - Ramos, Fernando (2012)
Quality and innovation of Higher Education is clearly pointing to a better pedagogic knowledge of the faculty members aiming at the academic success of the students. This aim requires, from the institution and teachers, a much greater involvement than what has been the case, at least, in Portuguese universities [6]. The University of Aveiro, Portugal, is engaged in taking advantage of all the opportunities to improve the quality of more than 40 undergraduate and 130 postgraduate programs currently being offered, and to wide the catalogue of choices of students by the promotion of ICT/Internet based programs [2]. One of the main constraints to overcome is the change of mind required from faculty staff, most of which is not familiarized with the functionalities of ICT/Internet based technologies to deploy flexible and studentcentred learning settings. The University of Aveiro is taking advantage of a major change in the European Higher Education landscape, the wiling to create a common European Higher Education space (Bologna Declaration), to induce changes in course design and delivery through the integration of ICT/Internet support. Furthermore, this paper presents and discusses a staff development program for faculty staff aiming to provide academics with essential skills in areas such as teaching best practices, curriculum design (student-centred), collaborative learning and the adoption of ICT/Internet technologies.